O efeito da tipologia de projetos na relação entre o gerenciamento de riscos e o sucesso de projetos gerenciados por abordagens ágeis: um estudo quantitativo - Fernandes, Pedro Jose Martins Alvarez (2020)
Even knowing that risk management influences the projects results, it is known that there are cases of failure whose main cause is the incorrect use of practices related to this knowledge area. It is also known that the agile approach of project management and its influence on project results has been widely studied, arousing the interest of the most diverse stakeholders involved with projects. However, the relationship between these areas is a phenomenon that is not consolidated in the literature specialized in project management. In order to understand this phenomenon and understand how the possible gaps between these different approaches occur, the objective of this study is to verify the relationship between risk management and the success of projects managed by agile approaches, as well as the moderating influence of the type of projects in the mentioned relationship. A quantitative methodology was selected, collecting data from a survey and using scales validated by previous studies. The data analysis was performed using the statistical technique of structural equation modeling, with moderation being validated by multigroup analysis, considering that the moderating variables are categorical. The final sample had 264 responses, generated by project professionals, not restricted to the project manager. The results demonstrated the influence of risk management on the success of projects, managed by traditional or agile approaches. In addition, it was found that the complexity of the project positively moderates the aforementioned relationship, when comparing the extreme groups of the approach used, which are, the Assembly and Array levels. However, the technology, innovation and pace variables did not have a moderating effect on the structural relationship involving the dependent and independent variables of the model, despite influencing the dimensions of project success, such as impact on the team and commercial success.